2018
DOI: 10.7567/jjap.57.052301
|View full text |Cite
|
Sign up to set email alerts
|

Planar structured perovskite solar cells by hybrid physical chemical vapor deposition with optimized perovskite film thickness

Abstract: The thickness of perovskite absorber layer is a critical parameter to determine a planar structured perovskite solar cell's performance. By modifying the spin coating speed and PbI 2 /N,N-dimethylformamide (DMF) solution concentration, the thickness of perovskite absorber layer was optimized to obtain high-performance solar cells. Using a PbI 2 /DMF solution of 1.3 mol/L, maximum power conversion efficiency (PCE ) of a perovskite solar cell is 15.5% with a perovskite film of 413 nm at 5000 rpm, and PCE of 14.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…[183] CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Ag 0.12 12.3% [184] CVD 3 FTO/c-TiO 2 /MAPI/Spiro/Ag 0.12 13.76% [185] CVD 2 FTO/c-TiO 2 /mp-TiO 2 /MAPI/ Spiro/Ag 1 13.8% [153] CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Au 0.24 13.99% * [186] 8.4 6.22% CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Ag 0.12 13.3%* [179] CVD 2 FTO/c-TiO 2 /mp-TiO 2 /MAPI/ Spiro/Au 0.11 17.8%* [187] CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Au 0.09 15.6%* [182] 15. 14.6%* [189] 0.1 16.6%* CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Au 0.09 15.5% [188] CVD 2 FTO/c-TiO 2 /MAPI/SWCNT/ Spiro/Au 0.25 7.9% [190] CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Au 0.09 15.5% [188] CVD 2 FTO/c-TiO 2 /CsFAPbIBr/Spiro/ Ag 0.09 18.2% [191] Samples with * are stabilized power conversion efficiency. All others are a maximum measurement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[183] CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Ag 0.12 12.3% [184] CVD 3 FTO/c-TiO 2 /MAPI/Spiro/Ag 0.12 13.76% [185] CVD 2 FTO/c-TiO 2 /mp-TiO 2 /MAPI/ Spiro/Ag 1 13.8% [153] CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Au 0.24 13.99% * [186] 8.4 6.22% CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Ag 0.12 13.3%* [179] CVD 2 FTO/c-TiO 2 /mp-TiO 2 /MAPI/ Spiro/Au 0.11 17.8%* [187] CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Au 0.09 15.6%* [182] 15. 14.6%* [189] 0.1 16.6%* CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Au 0.09 15.5% [188] CVD 2 FTO/c-TiO 2 /MAPI/SWCNT/ Spiro/Au 0.25 7.9% [190] CVD 2 FTO/c-TiO 2 /MAPI/Spiro/Au 0.09 15.5% [188] CVD 2 FTO/c-TiO 2 /CsFAPbIBr/Spiro/ Ag 0.09 18.2% [191] Samples with * are stabilized power conversion efficiency. All others are a maximum measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al [188] found that the best devices required a final MAPI thickness of roughly 300 nm to achieve g = 15.5% for small device areas. Wei et al [188] found that the best devices required a final MAPI thickness of roughly 300 nm to achieve g = 15.5% for small device areas.…”
Section: Perovskite Deposition Typementioning
confidence: 99%
See 1 more Smart Citation
“…16,17,43 The layer thickness of the perovskite is determined by the complete reaction of the inorganic layer, due to a diffusion barrier. 8,34,66 Recently RbI, SrI 2 , and KI have been added into the PbI 2 inorganic layer to tune the composition of the resulting lm. 36,44,65 On the other hand, a gradient composition can be formed by deposition of the CsBr/PbBr 2 inorganic layer with the FAI organic vapor (Fig.…”
Section: Morphology and Composition Of The Inorganic Layermentioning
confidence: 99%
“…16,17,43 The layer thickness of the perovskite is determined by the complete reaction of the inorganic layer, due to a diffusion barrier. 8,34,66…”
Section: Factors Influencing the Perovskite Layer Quality And Device ...mentioning
confidence: 99%